Polymorphism of R353Q (rs6046) in factor VII and the risk of myocardial infarction: A systematic review and meta-analysis. Issue 39 (September 2018) - Huang, Haoming; Long, Wenjie; Zhao, Weixuan; Zou, Ling; Song, Yudi; Zuo, Junling; Yang, Zhongqi
Abstract: Objective: Genetic components substantially contribute to the development of myocardial infarction (MI), and R353Q polymorphism (rs6046) in FVII gene has been suspected to be associated with the risk of MI. Methods: A meta-analysis was conducted on the links between R353Q polymorphism and the susceptibility of MI. A comprehensive literature search was performed on 8 electronic databases. The main effects of the genotypes were estimated using a logistic regression approach. The odds ratios with 95% confidence intervals were calculated using the conventional summary method meta-analysis. The possible sources of heterogeneity among the included studies were explored using meta-regression analysis and subgroup analysis. Results: A total of 18 eligible case-control studies, comprising of 4701 cases and 5329 controls, were included. No overall statistical relationship was identified between R353Q and MI by any of the genetic models. The meta-regression demonstrated that the Asian population, body mass index (BMI) category, and diabetes affected the heterogeneity. In addition, subgroup analyses showed that heterogeneities were identified in Asian population and BMI category, which highly agree with the results of meta-regression. Conclusions: The current meta-analysis suggested that R353Q polymorphism was not associated with the MI risk. Asian population, BMI category, and diabetes might be related to the incidence of MI. However, large-scale, case-control studies with rigorous designs are essential to provide accurate evidence. Abstract : Supplemental Digital Content is available in the text